Modern tendencies in development of local self-government in Republic of Kazakhstan - Sadyrbaev Е.А. (BUKETOV BUSINESS REVIEW, 2017)
In the article the pressing questions of development of local self-government are considered in Republic of Kazakhstan on the modern stage. The feature of the reforms carried out presently is the considerable strengthening of financial independence of organs of local self-government. It is constrained, foremost, with introduction of independent budget at the level of local self-government and introduction of «institute of community property of local self-government». Experience of reforms of local self-government in the countries considered in the article was studied and used for forming of the modern Kazakhstan model of local selfgovernment. In particular, what a leader of local government (and what procedures must be must provide efficiency of executive power at local level. The modern stage of development of local self-government in Republic of Kazakhstan is accompanied by important reforms and changes in a legislative base. The result of the offered measures in the end will be realization of politics of development of local self-government, that in turn will result in creation of the system of cooperation of population, local self-government and state power. All of it will allow to provide independence of decision the population of questions of local value, account of opinion of population at the decision of questions, directly affecting interests of population of corresponding territories.